كشف التنظيم الذاتي في استراتيجيات القراءة باللغة العربية لدى الناطقين بغيرها : دراسة تحليلية - Adibah binti Ahmad (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
Self-regulation is a powerful boost in driving students' motivation for learning, because it refers to self-generated thoughts, feelings, and behaviors that aim to achieve goals and students become more self-reliant than teachers, and are hard-working to learn because they understand their strengths and weaknesses. Studies in the field of second and foreign language learning have benefited from the concept of self-regulation and its relation with language learning strategies, and it is called self-regulated learning strategies. This research aims to identify the problems faced by students when reading the texts of the Arabic language, and then to determine the extent to which students use the self-regulated learning strategies to read texts in Arabic. The frequency of how students use the strategies was measured based on three basic meta-strategies; planning, observation, and evaluation. This research adopted the qualitative method by using semi-structured interview for data collection. The participants were six female students majoring in Arabic language from International Islamic University in Malaysia. This research has found two new problems when students read Arabic language text: lack of understanding of the culture of the Arabs and non-exposure to the Arab environment. This research also identified that students used self-regulated learning strategies during reading in Arabic in all aspects of planning, observation and evaluation strategies in which planning is the most frequent strategy used by the participants. In conclusion, the research recommends that students should be interested in using self-regulation to improve reading skills in Arabic to ensure life-long learning.